Nilai Integrasi Islam dan Sains di Lembaga Pendidikan Islam di Indonesia : Sekolah Islam Terpadu, Madrasah dan Pesantren - Hantika Aulia; Abu Anwar; Kuncoro Hadi (Tafhim Al-'Ilmi, 2022)
AbstractThis study aims to find out about the integration of Islam and science in Islamic educational institutions such as Integrated Islamic Schools (SIT), Madrasas and Islamic Boarding Schools. This type of research is library research. And the results show that all Islamic educational institutions have attempted to integrate Islam and science in the curriculum at their respective institutions, both written curriculum and through hidden curriculum. Each institution has its own way and method in integrating Islamic values into general subjects, such as in an integrated Islamic school. One form of integration that is carried out is to integrate the 2013 curriculum that they use in relation to their religious knowledge and there are many other forms of integration carried out by educational institutions, each of which has a different way and method. Keywords: Integration of Islam, Islam and Science, Religious and Secular